Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1126/science.8266098
|View full text |Cite
|
Sign up to set email alerts
|

A Covalent Enzyme-Substrate Intermediate with Saccharide Distortion in a Mutant T4 Lysozyme

Abstract: The glycosyl-enzyme intermediate in lysozyme action has long been considered to be an oxocarbonium ion, although precedent from other glycosidases and theoretical considerations suggest it should be a covalent enzyme-substrate adduct. The mutation of threonine 26 to glutamic acid in the active site cleft of phage T4 lysozyme (T4L) produced an enzyme that cleaved the cell wall of Escherichia coli but left the product covalently bound to the enzyme. The crystalline complex was nonisomorphous with wild-type T4L, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
217
1
5

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(231 citation statements)
references
References 34 publications
5
217
1
5
Order By: Relevance
“…With the notable exception of M106K, each of the variants constructed here has activity within about a factor of two equal to that of WT*. In an adduct of T4 lysozyme with an extended peptidoglycan cell-wall fragment, the side chain of Met 106 makes van der Waals contacts with the peptidic part of the fragment ( Kuroki et al, 1993). In the structure of M106K (Fig.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…With the notable exception of M106K, each of the variants constructed here has activity within about a factor of two equal to that of WT*. In an adduct of T4 lysozyme with an extended peptidoglycan cell-wall fragment, the side chain of Met 106 makes van der Waals contacts with the peptidic part of the fragment ( Kuroki et al, 1993). In the structure of M106K (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…4B) the €-amino group of Lys 106 occupies a position that would potentially interfere with bound substrate. Possible steric interference was checked by super-imposing the structure of M106K on the lysozyme-peptidoglycan complex described by Kuroki et al (1993). ence between M106K and bound substrate could explain the reduction in activity for this mutant.…”
Section: Discussionmentioning
confidence: 99%
“…As concerns the slightly twisted boat conformation adopted by the castanospermine in the MutB⅐castanospermine structure (Fig. 5C), it may be the precursor of the transition state, assumed to be in a half-chair conformation (51,52). In the latter the glycosidic linkage at the anomeric carbon would be in an axial position, which is needed for the terminal glycosyl residue to be completely enclosed in the pocket with the nucleophilic Asp 200 adjacent to C1 and to allow the aglycon to depart following bond cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance of the enzyme's function to several nonconservative substitutions (Asp 20-Cys and Asp 20-Ala), as well as the conservative substitution Asp 20-Glu (Anand et al, 1988;Rennell et al, 1991), indicated a less critical role for the Asp 20 side-chain carboxylate. A recent structure of a quasi-stable covalent adduct between a peptidoglycan substrate and several T4 lysozyme variants has led to a revision of the role for the Asp 20 carboxylate (Kuroki et al, 1993(Kuroki et al, , 1995. This residue seems to optimize the enzyme's binding of the transition state, rather than playing a pivotal catalytic role.…”
Section: Suppressible Deleterious Priman Substitutionsmentioning
confidence: 99%